The general or the special - which? - Oldham, Kate (My University, 1892)
Introduction: This subject is one of great importance and one that is receiving much discussion and comment at the present day, not merely for the sake of argument, as with some other much discussed subjects, but because there is much depends upon the course which we choose for pursuit through life. One of the most important questions that comes to us, sooner or later in life, is: “What can I best do to use my talents.” This question many never answer, but go through life wondering what their talents are. Sometimes we hear this subject discussed by people who set forth in glowing language the many advantages of specialism, never referring to the fact that there are disadvantages as well, and sometimes by people who are in favor of a general education for everyone and can see no good to be gained by specialism, but my place is to treat the subject without any partiality for either side, after a fair look at both. We have seen that as civilization advances the tendency toward specialism grows greater.
Citation: Oldham, Kate. The general or the special - which?. Senior thesis, Kansas State Agricultural College, 1892.
Morse Department of Special Collections
Keywords: Specialization; Education; Opinion; Theses; Manuscripts (documents)